Uso do pentóxido de nióbio para aplicação como substrato de antenas de microfita - Souza, Danilo de (Universidade Federal Rural do Semi-Árido, 2015)
This work studied the application of niobium pentoxide (Nb2O5) individually as substrate of microstrip antennas, when processed by powder technology. Powder with a particle size D50 of 40 𝜇m Nb2O5 was compressed in the pressure of 55 MPa, 111 MPa and 166 MPa and was sintered at temperatures of 800 ° C, 900 ° C, 1000 ° C and 1100 ° C for 4 h. Subsequently, the processed samples were characterized electricaly, physicaly and mechanicaly. In electrical characterization were obtained they loss tangent values and permittivity in two frequency bands (0,2 GHz to 4,0 GHz and 8,2 GHz to 12,4 GHz). In mechanical characterization, the tensile strength limit was calculated indirectly by diametrical compression test. In the physical characterization, their porosity, mass percentage variations and dimensional variations values were calculated. In addition, samples were characterized by the methods of X-ray diffraction, scanning electron microscopy and energy dispersive spectroscopy. Devices were also made with the produced substrates. These were characterized in the frequency range of 2,0 GHz to 14,0 GHz. Subsequently, several observations and conclusions were made. Among the main ones are: all made devices functioned as an antenna; the variation of the parameters of the manufacturing process resulted in changes in the electrical properties of the substrates, and consequently made the operating parameters antennas; all of the substrates produced seemed slightly weak and little mechanically resistant; the values of permittivity and loss tangent were according with the indications of the bibliography
Use of niobium pentoxide for use as a substrate antenna microstrip
Keywords: Communications systems; Automation systems; Niobium pentoxide; Microstrip antennas; sintering; Sistemas de comunicação; Sistemas de automação; Pentóxido de nióbio; Antenas de Microfita; Sinterização; ENGENHARIAS::ENGENHARIA ELETRICA